Cognitive, behavioral and socio-communication skills as predictors of response to Early Start Denver Model: a prospective study in 32 young children with Autism Spectrum Disorder - Asta, Lisa; Di Bella, Tiziana; La Fauci Belponer, Francesca; Bruschetta, Marianna; Martines, Silvia; Basile, Enrica; Boncoddo, Maria; Bellomo, Fabiana; Cucinotta, Francesca; Ricciardello, Arianna; Turriziani, Laura; Colombi, Costanza; et al. (Frontiers in Psychiatry, 2024)
Introduction The effectiveness of early interventions in young autistic children is well established, but there is great interindividual variability in treatment response. Predictors of response to naturalistic developmental behavioral interventions (NDBI), like the Early Start Denver Model (ESDM), are needed. Methods We conducted an exploratory study to prospectively seek predictors of response in 32 young children treated with ESDM after receiving an ASD diagnosis. All children were less than 39 months old (mean age: 29.7 mo), and received individualized ESDM for nine months. Tests were administered at the beginning, after 4 months, and at the end of treatment. Results Four children (12.5%) were “strong responders”, 8 children (25.0%) were “moderate responders”, and 20 children (62.5%) were “poor responders”. A more favorable response to ESDM was significantly predicted by higher PEP-3 Expressive Language, Receptive Language, Cognitive Verbal/Preverbal, Visuo-Motor Imitation scores, higher GMDS-ER Personal/Social, and VABS-II Communication scores, by lower ADI-R C restricted/stereotypic behaviors, and by joint attention level. Discussion Most predictors showed a linear association with increasing response to ESDM, but GMDS-ER Personal-Social and joint attention level predicted strong response, while PEP-3 receptive language equally predicted moderate or strong response. Although larger samples will be necessary to reach definitive conclusions, in conjunction with prior reports our findings begin providing information able to assist clinicians in choosing the most appropriate treatment program for young autistic children.